ELECTRICAL INSTABILITY OF MYOCARDIUM IN YOUNG MEN WITH ARTERIAL HYPERTENSION AND OCCUPATIONAL STRESS - I. V. Osipova; O. N. Antropova; K. I. Shakhmatova; V. D. Kondakov (Российский кардиологический журнал)
Aim. To evaluate prevalence of electrical instability of the heart in persons with stressogenic professions by a complex evaluation of the parameters of clinical and functional methods of investigation.Material and methods. Totally 154 men included with AH of I-II stages; first group consisted of 78 motormen and their assistants having stressogenic profession, second grup consisted of 76 persons with minimal psychoemotional tension. A clinical and functional investigation was performed.Results. In 1st group "possible existence" of delayed atrial and ventricular potentials was twice and three times (resp.) more prevalent comparing to the 2nd (with p=0,0001 and p=0,0002, resp.). A rigid circadian index in the 1st group was 1,7 times more prevalent (Х2=10,5; p<0,001). In those having AH with concomitant chronic gastritis and gastric or duodenal ulcer disease the circadian rigidity was 1,6 times more prevalent (x2 =5,9; p<0,05) in the 1st group. In first stage AH the shift of vagosympathetic balance to sympathic type is more common for the 1st group than for the 2nd.Conclusion. In young men with AH and occupational stress comparing to men with low — stress profession the signs of electrical instabilty are more common.